Recovery of conduction following high power short duration approach in radiofrequency catheter ablation for atrial fibrillation: a single-center experience. (14th October 2021) - Mohanty, S; Trivedi, C; Della Rocca, D G; Gianni, C; MacDonald, B; Mayedo, A; Burkhardt, J D; Bassiouny, M; Gallinghouse, G J; Horton, R; Al-Ahmad, A; Di Biase, L; et al.
Abstract: Introduction: High-power short-duration (HPSD) ablation is currently being adopted by many as the preferred procedural technique in atrial fibrillation (AF). However, the optimal duration of energy delivery to successfully create a durable lesion is not clear yet. Purpose: We evaluated the association of electrical reconnection with lesion-duration in HPSD ablation. Methods: Consecutive AF patients undergoing repeat procedure after a prior HPSD ablation with or without isolation of left atrial appendage (LAA) and coronary sinus (CS) were included in this analysis. HPSD ablation was defined as ablation with maximum temperature setting at 420C and power delivery at 45 W for 10–15 sec (5 seconds in the CS area and posterior wall near the esophagus). In some patients a mechanical esophageal deviation tool was used to deflect the esophagus away from the ablation site. Results: A total of 2249 AF patients (with LAA and CS isolation: 1451; without LAA and CS isolation: 798) receiving redo ablation after a prior HPSD procedure were included in the analysis. At the prior procedure with the HPSD approach, mean duration of ablation was significantly shorter in the area facing the esophagus compared to elsewhere (5.2±1.5 vs 12.5±1.7 seconds, p<0.001). Application duration was reduced to <10 sec to avoid overheating and steam pops in 1221 (84%) patients receiving LAA and CS isolation. At the redo, recovery of conduction was noted in the CS (592, 40.8%), LAA (493, 34%), and PV and left atrial posterior wall (LAPW) (310, 13.8%). Of the 310 patients with LAPW reconnection, 91% (n=282) had the conduction recovered in the area facing the esophagus. In 73 patients, esophageal displacement device was used during the prior HPSD ablation. Average duration of ablation lesions in LAPW among those 73 patients was 9.2±2 seconds. PV-LAPW reconnection was observed in 3/73 (4.1%) patients. Conclusion: HPSD ablation with lesion duration of <10 sec was associated with conduction recovery in the LAA, CS and the LAPW area facing esophagus. Funding Acknowledgement: Type of funding sources: None.